Term variation in specialised corpora : characterisation, automatic discovery and applications - Daille, Béatrice (Terminology and lexicography research and practice, 2017)
This book addresses term variation which has been a very important topic in terminology, computational terminology and natural language processing for up to twenty years. This book presents the first complete inventory of term variants and the linguistic procedures that lead to their formation. It also takes into account issues raised by multilingual applications and presents ways to detect variants in five different languages: French, English, German, Spanish and Russian. The book provides insights into the following issues: What is a variant? What are the main linguistic mechanisms involved in the transformation of base terms into variants? How can variants be automatically detected in texts? Should variation be taken into account in natural language processing applications? This book is targeted at terminologists and linguists interested in term variation as well as researchers in natural language processing and computer science that must handle term variants in different kinds of applications.